Analisis Pengelolaan Aset pada Bagian Keuangan dan Aset Dinas Kesehatan Kota Medan - Lita Chairunnisa; Arnida Wahyuni Lubis (Jurnal Mutiara Ilmu Akuntansi, 2024)
Any money or tangible or intangible asset owned by a person or business organization and whose value will benefit all of them in the future is considered an asset. Regional capital asset management aims to increase the effectiveness, efficiency and added value of asset management. Effective management of regional assets is critical to converting them into capital that helps local government grow. Apart from reviewing the completeness of sources and points of view, the aim of this research is to examine the planning, procurement, administration, reporting and monitoring of assets at the Medan City Health Service with regional asset management being implemented. A qualitative approach is used in this kind of research. The Medan City Health Service is the place where this research was conducted. This research uses a triangulation approach using observation, interviews, document analysis, and online research. Research findings show that there are deficiencies in asset planning, acquisition, management, reporting and monitoring. In particular, all regulations in Government Law Number 19 of 2016 have been implemented correctly and precisely; However, the implementation of this law is still not in accordance with property users.